Non-refractive complications of refractive surgery in patients with iridocorneal endothelial syndrome - T.N. Yur'ieva; O.V. Pisarevskaya (Офтальмохирургия)
Purpose. To present clinical cases of keratorefractive surgery in patients with iridocorneal endothelial syndrome. Material and methods. The examination and symptomatic treatment of two patients who underwent laser keratorefractive surgery for myopia correction was carried out. In the postoperative period, one of the operated eyes had low visual acuity, diffuse corneal edema, decompensation of IOP of unclear genesis. Results. The consistent use of standard (biomicroscopy, ophthalmoscopy, gonioscopy) and highly informative methods of examination (OCT of the anterior segment of the eye, UBM, endothelial microscopy) made it possible to diagnose iridocorneal endothelial syndrome in both cases. Drug hypotensive therapy in one case and trabeculectomy in the other allowed to restore the transparency of the cornea and improve visual acuity. Conclusion. Manifest changes in the anterior segment of the eye in many syndromes accompanied by the formation of glaucoma make it possible to identify hydrodynamic disorders at the earliest stages and prevent the destructive effect of increased IOP. The complex application of modern imaging methods provides an objective assessment of pathological changes in the eye, and allows you to determine indications and contraindications to refractive surgery.